Controlled Growth and Cathodoluminescence Property of ZnS nanobelts with Large Aspect Ratio - Wu, Xiang; Lei, Ying; Zhang, Yufeng; Qu, Fengyu (Nano-Micro Letters, 2014)
ZnS nanobelts with large aspect ratio are successfully synthesized on a large scale through thermally evaporating of ZnS powder with a trace of SnO2 powder using gold coated Si wafer as the substrate at 1100°C. The results indicate that the as-obtained ZnS nanobelts are about 10 nm in thickness and hundreds of micrometers in length, and the aspect ratio reaches more than 104. Substrate dependent experiments are conducted to better study the growth mechanism of the ZnS nanobelts. Subsequently, optical properties of the as-synthesized ZnS nanobelts are also investigated by using a cathodoluminescence (CL) system, which shows the existence of a strong ultraviolet emission at 342 nm and two poor emission peaks at 522 nm and 683 nm at room temperature, respectively.